Does Ambroxol alleviate kidney ischemia-reperfusion injury in rats? - ÇETİNEL, ŞULE (My University, 2022)
Objective(s): Ischemia-reperfusion injury is a life-threatening clinical problem that can occur after transplantation or a number of clinical procedures. The purpose of the study was to investigate the effects of Ambroxol on kidney damage caused by experimentally induced ischemia-reperfusion injury in rats.
Keywords: Tıp; Temel Eczacılık Bilimleri; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Basic Pharmaceutics Sciences; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Farmakoloji (tıbbi); İlaç Rehberleri; Pharmacy; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Research and Theory; Reviews and References (medical); Pharmacology (medical); Drug Guides